TNF‐α promotes invasive growth through the MET signaling pathway. Issue 2 (26th September 2014) - Bigatto, Viola; De Bacco, Francesca; Casanova, Elena; Reato, Gigliola; Lanzetti, Letizia; Isella, Claudio; Sarotto, Ivana; Comoglio, Paolo M.; Boccaccio, Carla
Abstract: The inflammatory cytokine Tumor Necrosis Factor Alpha (TNF‐α) is known to trigger invasive growth, a physiological property for tissue healing, turning into a hallmark of progression in cancer. However, the invasive response to TNF‐α relies on poorly understood molecular mechanisms. We thus investigated whether it involves the MET oncogene, which regulates the invasive growth program by encoding the tyrosine kinase receptor for Hepatocyte Growth Factor (HGF). Here we show that the TNF‐α pro‐invasive activity requires MET function, as it is fully inhibited by MET‐specific inhibitors (small‐molecules, antibodies, and siRNAs). Mechanistically, we show that TNF‐α induces MET transcription via NF‐κB, and exploits MET to sustain MEK/ERK activation and Snail accumulation, leading to E‐cadherin downregulation. We then show that TNF‐α not only induces MET expression in cancer cells, but also HGF secretion by fibroblasts. Consistently, we found that, in human colorectal cancer tissues, high levels of TNF‐α correlates with increased expression of both MET and HGF. These findings suggest that TNF‐α fosters a HGF/MET pro‐invasive paracrine loop in tumors. Targeting this ligand/receptor pair would contribute to prevent cancer progression associated with inflammation. Highlights: TNF‐α promotes cell invasion, which can be prevented by MET inhibition. TNF‐α induces MET expression in cancer cells. TNF‐α exploits a MET signaling pathway leading to E‐cadherin downregulation. TNF‐α induces expression of the MET ligand HGF in fibroblasts. In colorectal cancer tissues, high TNF‐α levels associate with high MET levels.